Computational Topology in Image Context 4th International Workshop, CTIC 2012, Bertinoro, Italy, May 28-30, 2012. Proceedings - Ferri, Massimo; Frosini, Patrizio; Landi, Claudia; Cerri, Andrea; Fabio, Barbara; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the proceedings of the 4th International Workshop on Computational Topology in Image Context, CTIC 2012, held in Bertinoro, Italy, in May 2012. The 16 papers presented in this volume were carefully reviewed and selected for inclusion in this book. They focus on the topology and computation in image context. The workshop is devoted to computational methods using topology for the analysis and comparison of images. The involved research fields comprise computational topology and geometry, discrete topology and geometry, geometrical modeling, algebraic topology for image applications, and any other field involving a geometric-topological approach to image processing.
Keywords: Computer science; Computer software; Computer simulation; Computer graphics; Computer vision; Optical pattern recognition; Algebraic topology; Computer Science; Image Processing and Computer Vision; Algorithm Analysis and Problem Complexity; Computer Graphics; Pattern Recognition; Algebraic Topology; Simulation and Modeling